Prevalence of caffeine use in elite athletes following its removal from the World Anti-Doping Agency list of banned substances - Del Coso, J. (Applied Physiology, Nutrition, and Metabolism, 2011)
The aim of this investigation was to determine the use of caffeine by athletes after its removal from the World Anti-Doping Agency list. For this purpose, we measured the caffeine concentration in 20 686 urine samples obtained for doping control from 2004 to 2008. We utilized only urine samples obtained after official national and international competitions. Urine caffeine concentration was determined using alkaline extraction followed by gas chromatography-mass spectrometry. The limit of detection (LOD) was set at 0.1 µg·mL-1. The percentage of urine samples below the LOD was 26.2%; the remaining 73.8% of the urine samples contained caffeine. Most urine samples (67.3%) had urinary caffeine concentrations below 5 µg·mL-1. Only 0.6% of urine samples exceeded the former threshold for caffeine doping (12 µg·mL-1). Triathlon (3.3 ± 2.2 µg·mL-1), cycling (2.6 ± 2.0 µg·mL-1), and rowing (1.9 ± 1.4 µg·mL-1) were the sports with the highest levels of urine caffeine concentration; gymnastics was the sport with the lowest urine caffeine concentration (0.5 ± 0.4 µg·mL-1). Older competitors (>30 y) had higher levels of caffeine in their urine than younger competitors (<20 y; p < 0.05); there were no differences between males and females. In conclusion, 3 out of 4 athletes had consumed caffeine before or during sports competition. Nevertheless, only a small proportion of these competitors (0.6%) had a urine caffeine concentration higher than 12 µg·mL-1. Endurance sports were the disciplines showing the highest urine caffeine excretion after competition.